Health systems, population and patient challenges for achieving universal health coverage for hypertension in Ghana. Issue 9 (31st July 2021) - Koduah, Augustina; Nonvignon, Justice; Colson, Abigail; Kurdi, Amanj; Morton, Alec; van der Meer, Robert; Aryeetey, Genevieve; Megiddo, Itamar
Abstract: Ghana has signed on to the United Nations Sustainable Development Goal to achieve universal health coverage (UHC), ensuring that all individuals receive the health care they require without financial hardship. Achieving that goal is a difficult task in any setting. The challenges are further exacerbated by a changing disease landscape, as the burden of non-communicable diseases (NCDs) is increasing and creating a dual burden along with infectious diseases. This study explores the existing health system for delivering hypertension care and the challenges of delivering UHC for hypertension in Ghana. Document analysis of national health reports, policies and legislations along with a review of research articles was conducted to explore the challenges of delivering UHC for NCDs in Ghana, and hypertension in particular. The main themes and indicators related to the challenges of delivering UHC for hypertension were mapped and analysed. The main challenges to delivering UHC for hypertension can be grouped into population and patient, on the one hand, and health system factors, on the other. Population and patient factors include (1) unhealthy lifestyles overburdening the health system, (2) poor health-seeking behaviour and (3) poor adherence to medication, which has led to uncontrolled cases and poor clinical outcomes even among treated patients with hypertension. Health system factors include (1) inadequate health system capacity for early diagnosis due to an increasing number of patients, (2) inequitable distribution of health care facilities affecting access, (3) financial sustainability of the National Health Insurance Scheme and delays in reimbursement of claims to facilities that affect the health system's ability to provide timely management of hypertension and (4) health care facilities and practitioners' use of non-standardized and uncalibrated blood pressure measuring equipment. Ghana therefore will need to make important decisions to overcome operational and financial challenges on its path to UHC.